Piezomagnetic parameters of the magnetostrictive materials - KACZKOWSKI, Z. (Archives of Acoustics, 1998)
Piezomagnetic parameters of magnetostrictive materials and transducers are discussed. Properties of piezomagnetic materials are characterized by piezomagnetic coefficients occurring in the piezomagnetic equations and by the other physical parameters and quantities. A measure of the effectiveness of energy conversion is a magnetomechanical coupling coefficient, which, in addition to mechanical, magnetomechanical and magnetic quality factors, a piezomagnetic dynamics and an electroacoustical efficiency, a vibration amplitude, etc., permits to compare properties of the piezomagnetic materials and transducers. These parameters are useful in both theory and applications of piezomagnetic materials and transducers.